Association of lower heart rate variability with neuroimaging markers for dementia‐related pathology: The Multi‐Ethnic Study of Atherosclerosis (MESA). (1st February 2022) - Sandler, Sebastian L.; Lockhart, Samuel N.; Hiatt, Kevin; Whitlow, Christopher T.; Rapp, Stephen R.; Sachs, Bonnie C.; Soliman, Elsayed Z.; Bertoni, Alain; Heckbert, Susan; Hughes, Tim M.; Schaich, Christopher L.
Abstract: Background: Lower heart rate variability (HRV), indicating worse cardiac autonomic function, is associated with cardiovascular risk factors for dementia. We hypothesized that lower HRV would be associated with neuroimaging biomarkers for dementia‐related pathology independent of cardiovascular risk factors. Method: During MESA Exam 6 (2016‐19), 256 white and African‐American Wake Forest site participants completed 3T brain MRI, and 159 further completed Aβ‐PET imaging. HRV was calculated as standard deviation of normal‐to‐normal intervals (SDNN) and root mean square of successive differences (RMSSD) from 10‐second electrocardiogram at Exam 1 (2000‐02) and Exam 5 (2010‐12). We related continuous (log2 ‐normalized) HRV to neuroimaging parameters including mean temporal lobe cortical thickness, neurite orientation dispersion and density imaging (NODDI) free water in gray (gmFW) and white matter (wmFW), and presence of cerebral microbleeds (CMBs), lacunes, and Aβ positivity (Pittsburgh Compound B SUVR ≥1.21) using multivariable linear and logistic regression, and examined race and sex interactions. To account for potential non‐linearity, we also considered the association of lowest quartile HRV to neuroimaging markers. Regression coefficients (β [95% CI]; standard deviation units) and odds ratios (OR [95% CI]) are adjusted for age, race, sex, education, systolic blood pressure, body mass index, smoking, hypertension medication use, diabetes, and APOE genotype. Result: In 254 participants (Exam 6 age 72.2±6.9 years; 58.7% female; 47.2% white) with HRV measurements, lower continuous Exam 1 SDNN (β = ‐0.23 [‐0.39, ‐0.07]) and RMSSD (β = ‐0.19 [‐0.33, ‐0.05]) were associated with higher wmFW. Interactions showed that CMBs were associated with lowest quartile Exam 1 SDNN (OR = 3.76 [1.15, 12.25]) and Exam 5 RMSSD (OR = 3.36 [1.07, 10.54]) in males only (sex interaction P <0.001), and with Exam 1 SDNN (OR = 2.58 [1.04, 6.45]) in African‐Americans only (race interaction P = 0.039). Lower HRV was not associated with cortical thickness or presence of lacunes. In 152 participants with Aβ‐PET, no associations with Aβ deposition were found. Conclusion: Lower HRV from up to 16 years prior may be associated with increased neuroinflammation as measured by free water in older adults. Associations between HRV and cerebral small vessel disease markers may differ by sex or race.